1987
DOI: 10.1139/v87-007
|View full text |Cite
|
Sign up to set email alerts
|

Studies in anthracyclinone synthesis. The oxidative decyanation route to aklavinone and 4,11-dideoxy-α-rhodomycinone

Abstract: The formal synthesis of aklavinone and the first synthesis of 4,11-dideoxy-α-rhodomycinone are described. Oxidative decyanation of the tetracyclic nitrile to the corresponding ketone using a strong base (LDA) constitutes an important strategy in the synthesis of both these compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…A shift in the maximum of u as temperature changed was observed, which means that the “cmc” diminished as temperature increased. This trend has been reported in 2BE + W as well . An analogous behavior (dependence) is suggested by the results of σ (see Table ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A shift in the maximum of u as temperature changed was observed, which means that the “cmc” diminished as temperature increased. This trend has been reported in 2BE + W as well . An analogous behavior (dependence) is suggested by the results of σ (see Table ).…”
Section: Discussionsupporting
confidence: 87%
“…The results are quite similar in some aspects to those found in some other systems such as phenol + water (P + W) 4 and 2-butoxyethanol + water (2BE + W) 5 and tert -butanol alcohol + water ( t B + W). , In these systems it has been shown that a kind of molecular aggregation is taking place. In P + W, the formation of phenol aggregates in the bulk of the one-liquid region was correlated with the surface saturation; in the 2BE + W mixture, several bulk properties showed peculiar behavior in a narrow concentration range where the component with a larger surface activity has saturated the vapor−liquid surface. Elizalde et al suggested that this concentration range should be considered as the equivalent to a cmc for this mixture because similar characteristics are present as in a typical system with micellization.…”
Section: Discussionmentioning
confidence: 99%
“…7 We could obtain the deoxo-derivative 6 by reductive removal of the carbonyl group of DIF-1 (1c) using triethylsilane in trifluoroacetic acid. 18 Compound 7, which has a methyl group instead of a methoxy group, was synthesized from orcinol instead of 5-methoxyresorcinol through the same synthetic route for DIF-1 (1c).…”
Section: Effects Of Dif-1 and Benzene Derivatives On The Innate Immunmentioning
confidence: 99%
“…In turn, alkylmalononitriles can be processed to malonic acid derivatives, 8 reduced to 1,3-diamines, 9,10 and undergo reductive 11,12 and oxidative decyanation reactions. [13][14][15][16][17][18] Most relevant to this work, Hayashi and co-workers developed an elegant oxidative protocol to convert malononitriles into amides or esters using molecular oxygen as the oxidant via the intermediacy of an acylcyanide (Scheme 1A). 19,20 We have been developing routes to a variety of complex scaffolds where alkylmalononitriles and/or alkylidenemalononitriles are key intermediates.…”
mentioning
confidence: 99%